Nonequilibrium readiness and precision of Gaussian quantum thermometers - Luca Mancino; Marco G. Genoni; Marco Barbieri; Mauro Paternostro (Physical Review Research, 2020)
The dimensionality of a thermometer is key in the design of quantum thermometry schemes. In general, the phenomenology that is typical of qubit-based quantum thermometry does not apply to infinite-dimensional ones. We analyze the dynamical and metrological features of nonequilibrium Gaussian quantum thermometers: On one hand, we highlight how quantum entanglement can enhance the readiness of composite Gaussian thermometers; on the other hand, we show that nonequilibrium conditions do not guarantee the best sensitivities in temperature estimation, thus suggesting the reassessment of some of the working principles underpinning quantum thermometry.